2013
DOI: 10.1200/jco.2013.31.4_suppl.450
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase I study of intravenous administration of reolysin in combination with irinotecan/fluorouracil/leucovorin (FOLFIRI) in patients (pts) with oxaliplatin-refractory/intolerant KRAS-mutant metastatic colorectal cancer (mCRC).

Abstract: 450 Background: Reolysin (reovirus serotype 3) contains a naturally occurring, ubiquitous, non-enveloped human dearing strain reovirus. Reovirus replicates in KRAS-mutant cells resulting in cell lysis. In phase I evaluation, CRC pts received single agent Reolysin with tumor stabilization and CEA response without significant toxicity. Reolysin and irinotecan (IRI) are synergistic in KRAS-mutant preclinical CRC models, providing rationale for this phase I study. Methods: This was a phase I dose escalation study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most common treatment‐related adverse events were nausea (79%), vomiting (58%), erythema at the injection site (42%), fevers/chills (37%) and transient flu‐like symptoms (32%) . Further phase I studies demonstrated the safety and broad anticancer activity of Reolysin in prostate cancer, malignant glioma, metastatic colorectal cancer, multiple myeloma and solid cancers . Multiple phase II studies have investigated intralesional injection of Reolysin together with local irradiation for the treatment of refractory or metastatic solid tumors, intravenous administration of Reolysin for metastatic melanoma and intravenous administration of Reolysin in combination with chemotherapy for head and neck cancer or lung squamous cell carcinoma …”
Section: Naturally Occurring Oncolytic Virusesmentioning
confidence: 99%
“…The most common treatment‐related adverse events were nausea (79%), vomiting (58%), erythema at the injection site (42%), fevers/chills (37%) and transient flu‐like symptoms (32%) . Further phase I studies demonstrated the safety and broad anticancer activity of Reolysin in prostate cancer, malignant glioma, metastatic colorectal cancer, multiple myeloma and solid cancers . Multiple phase II studies have investigated intralesional injection of Reolysin together with local irradiation for the treatment of refractory or metastatic solid tumors, intravenous administration of Reolysin for metastatic melanoma and intravenous administration of Reolysin in combination with chemotherapy for head and neck cancer or lung squamous cell carcinoma …”
Section: Naturally Occurring Oncolytic Virusesmentioning
confidence: 99%
“…Reovirus has now undergone further evaluation in phase I and II clinical trials across a range of indications; summarised in Table 1. Historically, the tumours most heavily targeted within the reovirus programme have been melanoma, myeloma and glioma [142,171,172], although trials have also included pancreatic, lung, breast, colorectal, prostate, and head and neck cancers [108,109,[173][174][175][176]. Initial trials deployed reovirus as a monotherapy, the majority utilising i.v.…”
Section: Reovirus Clinical Trialsmentioning
confidence: 99%
“…Furthermore, reovirus serotype 3 has been studied in a phase I trial of patients with mCRC and results suggest that patients mounted an adequate immune response resulting in robust lysis of mCRC cells [ 110 ]. Another phase I trial of reovirus serotype 3 has shown to be safe and well-tolerated with FOLFIRI co-treatment in KRAS mutant mCRC patients who had progression of disease on prior chemotherapy [ 111 ]. Ongoing trials continue to assess the safety and tolerability of various OVs in the treatment of CRC, but they have not yet succeeded to the advanced phases.…”
Section: Novel Therapeutic Modalitiesmentioning
confidence: 99%